Q-Test (Quran Test): Sebuah Sistem Tes Kompetensi Membaca Al-Quran - Bairus Salim (Balitbangda Provinsi Lampung, 2017)
Reading Al-Quran competency was one of the spiritual intelligence benchmarks that became the greatest goal of national education as mandated by the Law of Government no. 20 of 2003 on the National Education System. To measure the competence of reading the Quran, a holistic, systemic andaccountable system of test wasrequired. Q-Test (Quran Test)wasdesignedto respond to these challenges. Q-Test was a system of reading Al-Quran competency test based on correct appraisal principles. As a system, the Q-Test contained the following specification components: (a) test material consisting of makhraj and character natures, tajwid, gharib, and fasahah, (b) test forms which included written tests and practice, ( c) testers, and (d) test equipment. Implementation of QTest was first performed in SMA Negeri 1 Metro. As anexample, theauthordescribed the results of Q-Test on students of class XI IPA 5. Of the 23 muslim learners who performed the Quran reading competence test obtained the following results: as many as 7 students (30 %) got Good score, 11 students 48%) got Enough value, and 5 students (22 %) got Less score.